Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for Dihydropyrimidine Dehydrogenase Genotype and Fluoropyrimidine Dosing: 2017 Update. Issue 2 (20th November 2017) - Amstutz, Ursula; Henricks, Linda M.; Offer, Steven M.; Barbarino, Julia; Schellens, Jan H.M.; Swen, Jesse J.; Klein, Teri E.; McLeod, Howard L.; Caudle, Kelly E.; Diasio, Robert B.; Schwab, Matthias
Abstract : The purpose of this guideline is to provide information for the interpretation of clinical dihydropyrimidine dehydrogenase ( DPYD ) genotype tests so that the results can be used to guide dosing of fluoropyrimidines (5‐fluorouracil and capecitabine). Detailed guidelines for the use of fluoropyrimidines, their clinical pharmacology, 1 as well as analyses of cost‐effectiveness are beyond the scope of this document. The Clinical Pharmacogenetics Implementation Consortium (CPIC ® ) guidelines consider the situation of patients for which genotype data are already available2 (updates available athttps://cpicpgx.org/guidelines/guideline‐for‐fluoropyrimidines‐and‐dpyd/ ).